LITERATURE REVIEW: POTENSI Cinnamomum zeylanicum DALAM MENINGKATKAN KUALITAS SPERMA MELALUI REGULASI STRES OKSIDATIF - Azzahra Noor Firanti; Yuni Ahda (JURNAL BIOSENSE, 2026)
Infertility is a reproductive health issue that affects many couples of reproductive age, and in males it is frequently associated with decreased sperm quality. One of the major contributing factors to impaired sperm quality is oxidative stress, which results from an imbalance between the production of reactive oxygen species (ROS) and the antioxidant defense system. This imbalance can damage sperm cell membranes, alter DNA integrity, and disrupt the process of spermatogenesis. This study aimed to review the potential of Cinnamomum zeylanicum in improving sperm quality through the regulation of oxidative stress. A literature review approach was employed by examining scientific publications obtained from Google Scholar and ResearchGate within the last ten years. Relevant studies were analyzed descriptively based on research design, observed sperm parameters, and the reported findings. The review indicates that Cinnamomum zeylanicum contains several bioactive compounds, including flavonoids, polyphenols, and cinnamaldehyde, which exhibit strong antioxidant activity. These compounds may reduce oxidative damage and protect sperm cells, thereby potentially improving sperm parameters such as count, motility, and viability.